Website-Based Teaching Materials Development in Information and Communication Technology Subjects at IPIEMS Surabaya High School - Firmansyah, Naufal Fikri; Atiqoh, Atiqoh; Hartono, Hartono (Green Publisher Indonesia, 2025)
This research aims to produce a product in the form of learning media, namely web-based learning media with Google Sites as a site creation tool. Then a media validation test was carried out to determine the feasibility and practicality of Google Sites web-based learning media in senior high school (SMA) Information and Communication Technology (ICT) learning. This type of research is development research with the ADDIE model which consists of five stages, namely, analysis, design, development, implementation and evaluation. Data collection techniques using questionnaires. The validator test results consist of six validators, namely, the content expert feasibility validator obtained an average percentage of 90%, the media expert feasibility validator obtained an average percentage of 95%, and the design expert feasibility validator obtained an average of 95%. The results of the content expert practicality validator test obtained an average percentage of 89%, the media expert practicality validator obtained an average percentage of 96.6%, and the design expert practicality validator obtained an average percentage of 96%. The results of small group trials obtained an average percentage of 82.9% and the results of large group trials obtained an average percentage of 81.8%. Based on the data that has been obtained, it can be concluded that learning media based on the Google Sites website for learning Information and Communication Technology (ICT) class 10 in Senior High Schools (SMA) is suitable for use in learning activities.